Polar bear puzzle - Lumry, Amanda; Hurwitz, Laura (Bellevue : Scholastic, 2007)
Riley, Uncle Max, Aunt Martha, and Cousin Alice meet in northern Canada, where they study and help polar bears that are wandering through towns while waiting for Hudson Bay to freeze over again so that they can hunt for seals.
T
"Smithsonian Institution"--Cover.
"Widlife Conservation Society"--Cover.
860
T
Keywords: Polar bears -- Fiction; Bears -- Fiction; Human-animal relationships -- Fiction; Animals -- Polar regions -- Fiction